2011
DOI: 10.1038/ncb2201
|View full text |Cite
|
Sign up to set email alerts
|

53BP1 nuclear bodies form around DNA lesions generated by mitotic transmission of chromosomes under replication stress

Abstract: Completion of genome duplication is challenged by structural and topological barriers that impede progression of replication forks. Although this can seriously undermine genome integrity, the fate of DNA with unresolved replication intermediates is not known. Here, we show that mild replication stress increases the frequency of chromosomal lesions that are transmitted to daughter cells. Throughout G1, these lesions are sequestered in nuclear compartments marked by p53-binding protein 1 (53BP1) and other chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
651
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 603 publications
(721 citation statements)
references
References 50 publications
51
651
2
2
Order By: Relevance
“…So far, pan-nuclear histone H2AX phoshorylation has been used as a surrogate marker, given that it is restricted to S-phase cells and is detected in cells that show RPA foci [10,[81][82][83]. An interesting alternative is the detection of 53BP1 bodies, large nuclear 53BP1 foci which accumulate preferentially at fragile sites in G1 cells after exposure to RS [84,85]. However, both strategies have their limitations and better biomarkers are needed for an accurate identification of RS.…”
Section: Targeting Rs In Cancer Treatmentmentioning
confidence: 99%
“…So far, pan-nuclear histone H2AX phoshorylation has been used as a surrogate marker, given that it is restricted to S-phase cells and is detected in cells that show RPA foci [10,[81][82][83]. An interesting alternative is the detection of 53BP1 bodies, large nuclear 53BP1 foci which accumulate preferentially at fragile sites in G1 cells after exposure to RS [84,85]. However, both strategies have their limitations and better biomarkers are needed for an accurate identification of RS.…”
Section: Targeting Rs In Cancer Treatmentmentioning
confidence: 99%
“…Jones et Jallepalli [23] ont aussi suggéré que l'apparition du chromothripsis puisse résulter de l'effet combiné des erreurs mitotiques de ségrégation, de l'instabilité chromosomique générée et du stress réplicatif qui en découle. Ce stress peut créer des points de cassure au niveau des origines de réplication [24]. Enfin, une étude récente a établi une corrélation entre l'inactivation du gène TP53, codant pour la protéine p53, et le chromothripsis chez des patients atteints du syndrome de Li-Fraumeni.…”
Section: Facteurs Causals Du Chromothripsisunclassified
“…The 53BP1 NBs colocalize with a range of markers that normally assemble in the vicinity of DSBs such as MDC1, g-H2AX, ATM, RNF8 and BRCA1. 88 53BP1 NBs were further found to colocalize with transcriptional regulatory OPT (Oct-1, PTF, transcription) domains, induced by micro-irradiation as well as ionizing radiation. 87 Consistently, 53BP1-OPT domains neither colocalize with RNA transcription initiation or elongation factors nor with transcriptionally incorporated 5-fluorouridine, showing that active transcription was not detectable at these sites.…”
Section: Processing Of Underreplicated Regions and Joint Molecules Inmentioning
confidence: 99%
“…87 Consistently, 53BP1-OPT domains neither colocalize with RNA transcription initiation or elongation factors nor with transcriptionally incorporated 5-fluorouridine, showing that active transcription was not detectable at these sites. 87 Inhibition of ATM showed that ATM activity is needed for the efficient formation of 53BP1 NBs in G1 87,88 TopBP1 forms foci in mitosis TopBP1 forms abundant foci at mitotic onset but only a small fraction of these turns into DNA bridges in anaphase, suggesting that DNA structures other that joint molecules can recruit TopBP1 at mitotic onset. Interestingly, Burgess et al have shown that chromatin condensation per se can trigger an initial DNA damage response, which results in the recruitment of several DDR factors including MDC1.…”
Section: Processing Of Underreplicated Regions and Joint Molecules Inmentioning
confidence: 99%
See 1 more Smart Citation